Measurement System Of Damage Road Surface Volume With Ultrasonic Sensor Based Atmega 328 - Ilham Adi Putra; Ena Suma Indrawati (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
As the main road that connects one region to another, damaged roads is a complex problem and causes huge losses, especially for road users. Therefore, in this study will be designed a system for measuring the volume of damage road surface by using ultrasonic sensors. This system uses ATMega 328 microcontroller interface and applications are made from Visual Basic 6. From this study, we got the best measurements results of road surface damage volume in a short time and the data stored on the pc directly get in Microsoft Excel format.